Enhanced Antifouling Properties of Carbohydrate Coated Poly(ether sulfone) Membranes - Colavita, Paula; Scanlan, Eoin (My University, 2015)
Polyethersulfone membranes (PES) were modified with biologically active monosaccharides and disaccharides using aryldiazonium chemistry as a mild, one step, surface modification strategy. We previously proposed the modification of carbon, metals, and alloys with monosaccharides using the same method; herein we demonstrate modification of PES membranes and the effect of chemisorbed carbohydrate layers on their resistance to biofouling. Glycosylated PES surfaces were characterized using spectroscopic methods and tested against their ability to interact with specific carbohydrate-binding proteins. Galactose, mannose and lactose modified PES surfaces were exposed to Bovine Serum Albumin (BSA) solutions to assess unspecific protein adsorption in the laboratory and were found to adsorb significantly lower amounts of BSA compared to bare membranes. The ability of molecular carbohydrate layers to impart antifouling properties was further tested in the field via long term immersive tests at a wastewater treatment plant. A combination of ATP content assays, infrared spectroscopic characterization and He-ion microscopy (HIM) imaging were used to investigate biomass accumulation at membranes. We show that, beyond laboratory applications and in the case of complex aqueous environments that are rich in biomass such as wastewater effluent, we observe significantly lower biofouling at carbohydrate modified PES than at bare PES membrane surfaces.
PUBLISHED
Keywords: Polyethersulfone membranes (PES); Polyethersulfone membranes (PES)